Reduction of Amyloid in the Brain and Retina After Treatment With IVIG for Mild Cognitive Impairment. (11th February 2020) - Kile, Shawn; Au, William; Parise, Carol; Sohi, Jaideep; Yarbrough, Tracy; Czeszynski, Alan; Johnson, Ken; Redline, Dan; Donnel, Tammy; Hankins, Andrea; Rose, Kimberley
Objective: To assess whether intravenous immunoglobulin (IVIG) in subjects with mild cognitive impairment (MCI) results in a reduction in amyloid in the central nervous system (CNS). Methods: Five subjects with MCI underwent baseline Florbetapir positron emission tomography and retinal autofluorescent imaging. All were administered IVIG (Octagam 10%) at 0.4 g/kg every 14 days for a total of 5 infusions. After 3 months, standard uptake value ratio (SUVR) and amyloid retinal deposits were reassessed. Results: Three subjects had a reduction in amyloid SUVR and all 5 subjects had a reduction in amyloid retinal deposits in at least 1 eye. Conclusions: A short course of IVIG over 2 months removes a measurable amount of amyloid from the CNS in persons with MCI.